2012
DOI: 10.1007/s00383-012-3084-8
|View full text |Cite
|
Sign up to set email alerts
|

Infantile pulmonary tuberculosis: the great mimic

Abstract: Infantile pulmonary/mediastinal tuberculosis may mimic congenital thoracic malformations. A review of contact history, investigations and imaging help to establish the tuberculous etiology, avoids surgical misadventures and prompts early antituberculous therapy to achieve a favorable outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In total, 67.39% of patients developed symptoms within 3 weeks of birth, and patients who developed symptoms in fewer than 7 days accounted for 19.56% of all patients with congenital tuberculosis. In addition, disseminated Bacilli Calmette Guerin (BCG) disease should be excluded [12]. Because BCG vaccination is completed within 24 h of birth in China, the onset time for disseminated BCG disease may overlap with that of congenital tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 67.39% of patients developed symptoms within 3 weeks of birth, and patients who developed symptoms in fewer than 7 days accounted for 19.56% of all patients with congenital tuberculosis. In addition, disseminated Bacilli Calmette Guerin (BCG) disease should be excluded [12]. Because BCG vaccination is completed within 24 h of birth in China, the onset time for disseminated BCG disease may overlap with that of congenital tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, due to differences in individuals’ immune functions, the time of symptom onset varied significantly ( Schaaf et al, 2010 ). Varik et al (2012) reported the symptoms of congenital tuberculosis occurred within 3 weeks after birth, and the average age of onset was 28 days. In our case, the 19-day-old male presented fever and tachypnea as well as signs of respiratory failure.…”
Section: Discussionmentioning
confidence: 99%